Seasonal variation in toxic steroidal alkaloids of foothill death camas (Zigadenus paniculatus). (June 2020) - Stonecipher, Clinton A.; Cook, Daniel; Welch, Kevin D.; Gardner, Dale R.; Pfister, James A.
Abstract: Death camas ( Zigadenus spp.) is a common poisonous plant in North America with plants occurring in a wide variety of habitats with species of toxic concern occurring primarily in meadows, grasslands, shrublands, and mountains. The toxicity of Zigadenus species has been attributed to a series of steroidal alkaloids. The objective of this study was to evaluate zygacine and total steroidal alkaloid concentrations in different plant tissues of Zigadenus paniculatus as a function of plant maturity. Death camas plants were collected at two locations at different developmental growth stages representing vegetative, flower, seed pod, and shattered seed pod stages. Zygacine represented greater than 50% of the total steroidal alkaloids at all developmental stages. In bulbs, total steroidal alkaloid and zygacine concentrations did not change significantly as a function of plant phenology, and concentrations were lower than what were observed in above ground plant parts. Total steroidal alkaloid and zygacine concentrations in above ground parts were highest at early vegetative growth stages and decreased over the growing season. In plant reproductive parts, total steroidal alkaloid and zygacine concentrations increased until maturity and then decreased as the plant senesced. The concentrations of steroidal alkaloids reported here suggest that the toxic risk associated with death camas is greatest in the early vegetative growth stages followed by the flower and pod stages. There is a toxic risk to livestock as long as the plant is present, and caution should be taken when grazing livestock in areas with death camas until the plant senesces. Highlights: Death camas alkaloids are highest in leaves at early vegetative growth stages. Alkaloids in death camas plants decrease over the growing season. Alkaloids in death camas reproductive parts increase until maturity and then decrease. Alkaloids in death camas bulbs do not change as a function of plant phenology.